1997
DOI: 10.1007/bf03013155
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tramadol and tramadol/droperidol mixture for patient-controlled analgesia

Abstract: MBCKB FRCA FFARCSI MRcv(UK) l~I-IlCa/vl(Anaes)To compare the analgesic efficacy and side effects of tramadol vs tramadol and droperidol for post-operative patient-controlled analgesia (PCA), Method: Randomised, double-blind study. Thirty-four patients undergoing elective colorectal or head and neck surgery were allocated to Group I (n = 18, PCA bolus I 0 mg tramadol ) or Group 2 (n = 16, PCA bolus I 0 mg trarnadol + 0. I mg droperidol). Anaesthesia was induced with fentanyl and thiopentone and maintained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 11 publications
1
16
0
2
Order By: Relevance
“…namic adverse effects have been reported with tramadol alone or with the tramadol-droperidol combination. [1][2][3]12,16,18 We observed a decrease in blood pressure and heart rate from the tenth minute onwards only in the tramadol-clonidine group. This decrease did not require any intervention and no such adverse effect was detected in the other groups.…”
Section: Objectif : Comparer Le Tramadol à La Combinaison De Tramadolmentioning
confidence: 63%
See 4 more Smart Citations
“…namic adverse effects have been reported with tramadol alone or with the tramadol-droperidol combination. [1][2][3]12,16,18 We observed a decrease in blood pressure and heart rate from the tenth minute onwards only in the tramadol-clonidine group. This decrease did not require any intervention and no such adverse effect was detected in the other groups.…”
Section: Objectif : Comparer Le Tramadol à La Combinaison De Tramadolmentioning
confidence: 63%
“…Studies using tramadol and tramadol-droperidol combinations found no significant sedation, 2,3,9,16,18 while all studies using clonidine have reported a prominent increase in sedation. 1,4,10,15,19 This leads us to believe that the significant increase in sedation observed in the tramadol-clonidine group was due to the addition of clonidine.…”
Section: Objectif : Comparer Le Tramadol à La Combinaison De Tramadolmentioning
confidence: 96%
See 3 more Smart Citations